Analisis Produktivitas Kerja Tenaga Medis dan Non Medis dengan Metode Time and Motion Study di Puskesmas Banguntapan II Bantul Yogyakarta Tahun 2021 - Rinawati (International Journal of Healthcare Research, 2021)
Health center health workers are the main resource to create a healthy community. Medical and non-medical personnel also play an important role in public health services. The Banguntapan II Health Center in Bantul has a wide working area so that it will be correlated with the availability of human resources at the Puskesmas both for the number of human resources, performance and productivity of the health services provided by the Puskesmas to the community, especially considering the current state of the COVID pandemic. The purpose of this study was to find out how the work productivity of medical and non- medical personnel with the time and motion study method at the Banguntapan II Health Center, Bantul, Yogyakarta in 2021. This type of research uses a combination method (Mixed Method Research) with quantitative and qualitative approaches with Explanatory Sequential Design. The number of respondents who were studied by total sampling technique was 41 people and the research subjects who were examined by quota sampling technique were 12 people, taken from medical and non-medical personnel at Banguntapan II Public Health Center, Bantul Yogyakarta. Work productivity at Banguntapan II Public Health Center is seen from the standard time for medical personnel totaling an average of 7 hours 3 minutes, and non- medical personnel totaling an average of 6 hours 39 minutes. The factor that affects the work productivity of medical and non-medical workers is the work environment. The results showed that medical and non-medical personnel at Banguntapan II Health Center had good work productivity. However, the Puskesmas needs to pay attention to the needs of non- medical personnel to maximize the program from Public Health Center.